2007
DOI: 10.1111/j.1479-828x.2006.00673.x
|View full text |Cite
|
Sign up to set email alerts
|

Misoprostol for termination of mid‐trimester post‐Caesarean pregnancy

Abstract: The use of misoprostol for mid-trimester pregnancy termination is not contraindicated in women with Caesarean scar and is effective and comparable with those in women without scarred uteri.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(19 citation statements)
references
References 14 publications
2
15
1
Order By: Relevance
“…Similar to other studies, 4,5,16,17 the present study also did not experience any serious complications.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar to other studies, 4,5,16,17 the present study also did not experience any serious complications.…”
Section: Discussionsupporting
confidence: 91%
“…In failed termination, additional vaginal misoprostol might work in some instances and can be tried. Similar to other studies, 4,5,16,17 misoprostol was equally safe and effective in scarred and non‐scarred uterus.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…While misoprostol is available in Egypt, Chapman et al [9] reported a higher incidence of uterine rupture and hemorrhage with this drug than with mifepristone for women with cesarean scars, whereas others have shown it to be relatively safe [7,12,13]. These conflicting reports have led to suggest that the safety of misoprostol is yet to be established for these women [14].…”
Section: Discussionmentioning
confidence: 95%
“…There, too, no cases of uterine rupture occurred. Bhattacharjee et al [14] used misoprostol vaginally or sublingually every 6 hours, up to a maximum of 24 hours. The dosage was 400 μg when the gestation duration was less than 20 weeks and 200 μg when it was 20 weeks or longer.…”
Section: Discussionmentioning
confidence: 99%